Análisis comparativo de métodos empírico-semi-empírico para estimar la evapotranspiración en la provincia de Loja - Moreno Romero, Luis Alfredo (2023)
Evapotranspiration is one of the most important variables in the field of agronomic sciences, so it is considered an important element to consider the water needs of crops, so that they can develop correctly. The research consists of calculating evapotranspiration using different semi empirical methods (Jensen-Haise, Hargreaves, Thornthwaite, Blaney-Morin) compared with the empirical method (Penman-Monteith) to estimate ETo in the province of Loja and its distribution over the cantons from the meteorological stations. The evapotranspiration by the semi-empirical methods was calculated using meteorological yearbooks, due to the low data requirements for applying the formulas. Unlike the Penman-Monteith method established by the FAO (Food and Agriculture Organization of the United Nations), which was obtained from the climatic data of the CHELSA page for a statistical series of 22 years, this way we compared them with the methods used for the calculation of evapotranspiration in the study area. As a result of the investigation, an approximation was obtained with the Jensen-Haise method with 84.19%, Hargreaves with 74.10%, Thornthwaite with 59.50% and Blaney-Morin with 41.82%; therefore, the first two semi-empirical methods can be considered for having a greater kinship with the Penman-Monteith method, but they should be taken into account when representing the ETo distribution on a map since it differs greatly in some cantons of Loja province.